Daidzein ameliorates doxorubicin-induced cardiac injury by inhibiting autophagy and apoptosis in rats. Issue 2 (21st December 2022) - Wu, Jinxia; Li, Kexue; Liu, Yan; Feng, Ailu; Liu, Chunyang; Adu-Amankwaah, Joseph; Ji, Miaojin; Ma, Yanhong; Hao, Yanling; Bu, Huimin; Sun, Hong
Abstract : Doxorubicin (Dox) is a classical antitumor antibiotic widely restricted for use due to its cardiotoxicity. Abstract : Backgrounds : Doxorubicin (Dox) is a classical antitumor antibiotic widely restricted for use due to its cardiotoxicity. Daidzein (Daid) is a soy isoflavone that enhances antioxidant enzyme systems and inhibits apoptosis to prevent cardiovascular diseases. In this study, we intended to assess whether Daid protects against Dox-induced cardiotoxicity and explored its underlying mechanisms. Methods : Male Sprague-Dawley (SD) rats were divided into five groups: control (Ctrl), 40 mg per kg per day Daidzein (Daid), 3 mg per kg per week doxorubicin (Dox), 20 mg per kg per day Daidzein + 3 mg per kg per week doxorubicin (Daid20 + Dox) and 40 mg per kg per day Daidzein + 3 mg per kg per week doxorubicin (Daid40 + Dox) groups. Cardiac function assessments, immunohistochemistry (IHC) and immunofluorescence (IF) analyses were initially performed in each group of rats. Secondly, the cell proliferative capacity analysis, AO staining, and LC3 puncta analysis were employed to evaluate the cellular response to Dox in H9c2 cells. Ultimately, the protein expressions of cleaved caspase3, LC3 II, Bcl-2, Bax, Akt, p-Akt, and cyclin D1 were examined by western blotting. Results : Pretreatment with a low dose of Daid rather than a high dose significantly enhanced cardiac function and alleviated histopathological deterioration of cardiomyocytes induced by Dox. Daid downregulated the protein levels of Bax, LC3 II, cleaved caspase3 and p-Akt, while up-regulating Bcl-2 and cyclin D1. The Akt agonist SC79 could invalidate all the protective effects of Daid both in vivo and in vitro . Conclusions : Daid reduced autophagy and apoptosis by inhibiting the PI3K/Akt pathway, thereby protecting the hearts from Dox-induced cardiac damage.